Polyvinyl alcohol fiber for in-situ synthesis of polycarboxylate superplasticizer on surface, and preparation method and application thereof
Patent Information
- Application Number
- CN202611158175.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-31
- Publication Date
- 2026-10-20
AI Technical Summary
[0010]综上所述,现有技术尚未能从根本上解决PVA纤维在UHPC中的分散性与界面协同优化问题:纤维改性方法多聚焦于单一目标的改进,要么降亲水、要么增界面,而将功能性减水剂本身作为纤维表面共价接枝物的研究仍有待进一步发展
1、本发明通过在纤维表面原位接枝PCE分子刷,利用PEO侧链的空间位阻效应在纤维之间建立“软屏障”,有效阻断了纤维表面羟基之间的氢键桥联通道,从分子层面消除了导致结球团聚的根本原因。采用本发明方法制备的功能化PVA纤维在UHPC基体中的分散系数FDC,较未改性纤维提升了9.6%~17.9%,纤维团聚现象显著减轻。
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of functional fiber technology for cement-based composite materials, and more particularly to a method for in-situ synthesis of polycarboxylate superplasticizer (PCE) on the surface of polyvinyl alcohol (PVA) fibers via surface-initiated free radical copolymerization, and the application of the functionalized polyvinyl alcohol fibers obtained therefrom in ultra-high performance concrete (UHPC). Background Technology
[0002] Ultra-High Performance Concrete (UHPC) is a new generation of cement-based composite material characterized by ultra-high strength, ultra-high toughness, and excellent durability. Its compressive strength is typically no less than 150 MPa, and its flexural strength no less than 25 MPa. It is widely used in major engineering projects such as bridge construction, offshore platforms, nuclear power plant containment structures, and national defense protection facilities. The low water-cement ratio, high cementitious material content, and high-density mix design of UHPC give it extremely excellent mechanical properties, but also bring a series of technical challenges that urgently need to be addressed. Among these, the dispersion problem of fiber-reinforced materials is particularly prominent.
[0003] Polyvinyl alcohol (PVA) fiber is one of the most commonly used organic reinforcing fibers in UHPC (Ultra-High-Performance PC). PVA fiber possesses advantages such as high tensile strength (typically ≥1500 MPa), high elastic modulus (approximately 38 GPa), and good alkali resistance and hydrophilicity. However, there are two interrelated core issues when practically applying PVA fiber to UHPC: First, the fiber dispersibility is poor. PVA fiber molecular chains are rich in secondary alcohol hydroxyl groups (-OH), exhibiting strong surface polarity and high hydrophilicity. When a large amount of PVA fiber is added to a UHPC mixture with a low water-cement ratio, the hydroxyl groups on the fiber surface interact through hydrogen bonds, resulting in a strong "balling effect." This leads to fiber agglomeration and entanglement, making it difficult to achieve uniform dispersion in the cement matrix. Fiber agglomeration not only introduces defects such as pores and weak interfaces into the matrix but also significantly deteriorates the workability of UHPC, manifested as decreased spreadability and increased flow resistance. To overcome this problem, in actual production, it is usually necessary to increase the dosage of polycarboxylate ester-based superplasticizer (PCE) to compensate for the loss of flowability caused by fiber agglomeration. However, this in turn causes a series of secondary problems such as delayed early hydration and increased costs.
[0004] Second, the fiber-matrix interface bonding is insufficient. Although the hydroxyl groups on the surface of PVA fibers can theoretically react with Ca in the CSH gel, a product of cement hydration,... 2+Ions form hydrogen and ionic bonds, providing some chemical bonding ability. However, in actual UHPC systems, due to the cumulative effect of local defects caused by poor dispersion, the interfacial transition zone (ITZ) between the fiber and cement matrix often exhibits high porosity and weak stress transfer efficiency. Studies have shown that the failure mode of unmodified PVA fibers in UHPC is mainly fiber pull-out rather than fiber fracture, indicating that the interfacial bond strength fails to fully utilize the fiber's own load-bearing potential.
[0005] To address the aforementioned issues, various methods for surface modification of PVA fibers have been developed in the existing technology, mainly including: (1) Physical coating method: such as coating the fiber surface with hydrophobic substances such as mineral oil and paraffin to reduce the hydrogen bonding force between fibers. The disadvantage of this method is that there is only physical adsorption between the coating and the fiber, which is easy to fall off during use, and the hydrophobic coating actually weakens the chemical bond between the fiber and the cement matrix.
[0006] (2) Silane coupling agent method: For example, PVA fibers are pretreated with γ-glycidoxypropyltrimethoxysilane (KH560), which causes the epoxy groups of the silane molecules to undergo a ring-opening reaction with the hydroxyl groups on the fiber surface, and the hydrolyzed silanol groups to form Si-O-Si chemical bonds with cement products. This method can improve the fiber-matrix interface adhesion, but the silane treatment itself does not have water-reducing and dispersing functions, and cannot solve the fiber agglomeration problem at the same time.
[0007] (3) Nanoparticle deposition method: such as using the sol-gel method to load nano-SiO2 particles or graphene oxide (GO) on the surface of PVA fibers, utilizing the high specific surface area and active functional groups of nanoparticles to strengthen the fiber-matrix interface. This method can significantly improve interface performance, but the process is complex and costly, and it also lacks the ability to actively disperse fibers.
[0008] (4) Nonionic surfactant treatment: For example, polyoxyethylene nonionic surfactants, such as polyoxyethylene (20) cetyl ether, are used to soak PVA fibers. The surfactant molecules occupy the hydroxyl sites on the fiber surface and weaken the internal hydrogen bonds between fibers, thereby inhibiting balling. The mechanism of this method is somewhat similar to that of the present invention, but it only uses ordinary surfactants rather than functional water-reducing agent molecules. It does not have the ability to plasticize and disperse cement particles, and the binding force between the surfactant and the fiber is weak. It mainly relies on hydrogen bond adsorption and is easily desorbed and ineffective in the alkaline cement pore solution environment.
[0009] On the other hand, polycarboxylate superplasticizers are currently widely used high-efficiency plasticizing additives in UHPC. Their typical structure consists of a main chain composed of poly(meth)acrylic acid with anionic carboxyl groups -COO. -PCE consists of comb-like side chains made of polyoxyethylene (PEO). PCE achieves efficient dispersion of cement particles through the electrostatic repulsion of the main chain carboxyl groups and the steric hindrance effect of the side chains. However, in conventional UHPC formulation processes, PCE is added to the system after being uniformly dissolved in the mixing water as an independent admixture; it has no direct chemical relationship with the fibers. In other words, the existing "PCE + PVA fiber" compound system is essentially still two independent additive components, each playing its own role without synergy.
[0010] In summary, current technologies have not fundamentally solved the problems of dispersion and interfacial synergistic optimization of PVA fibers in UHPC: fiber modification methods mostly focus on improving single objectives, either reducing hydrophilicity or increasing interfacial density, while research on using functional water-reducing agents themselves as covalent grafts on fiber surfaces still needs further development. Therefore, developing a novel functional fiber that can integrate PVA fibers and polycarboxylate-based water-reducing agents at the molecular level is of significant scientific and practical value for overcoming the current bottlenecks in UHPC fiber reinforcement technology. Summary of the Invention
[0011] To achieve the above objectives, this invention provides a polyvinyl alcohol fiber synthesized from polycarboxylate superplasticizers in situ on the surface, its preparation method, and its application. The core concept of this preparation method is to use the abundant hydroxyl groups (-OH) on the PVA fiber surface as natural chemical handles. First, controllable free radical polymerization initiation sites are introduced on the fiber surface through activation treatment. Then, a surface-initiated free radical copolymerization reaction is directly carried out in an aqueous system, allowing the carboxyl monomers and polyether macromonomers constituting the polycarboxylate superplasticizer to "grow" in situ from the fiber surface, ultimately forming a polycarboxylate superplasticizer molecular brush structure covalently anchored to the fiber surface.
[0012] To achieve the above objectives, the present invention provides the following technical solution: In a first aspect, the present invention provides a method for preparing polyvinyl alcohol fibers with polycarboxylate-based water-reducing agents synthesized in situ on the surface, comprising the following steps: 1) Polyvinyl alcohol fibers are immersed in a solution containing an activator to perform surface hydroxyl activation treatment, thereby introducing free radical polymerization initiation sites on the fiber surface to obtain fibers with initiation sites functionalized. 2) The fiber obtained in step 1) is placed in an aqueous reaction system containing carboxyl monomers and polyether macromonomers. Under the action of a water-soluble initiator, a surface-initiated free radical copolymerization reaction is carried out, so that the polycarboxylate superplasticizer is grafted and grown in situ from the fiber surface in the form of covalent bonds, forming a functionalized fiber with a polycarboxylate superplasticizer molecular brush on the surface. 3) The fibers obtained in step 2) are washed and dried to obtain polyvinyl alcohol fibers with polycarboxylic acid water-reducing agents synthesized in situ on the surface.
[0013] Furthermore, in step 1), the polyvinyl alcohol fibers are pre-cleaned and solvent-replaced before the surface hydroxyl activation treatment; the specific steps are as follows: The fibers were ultrasonically cleaned with anhydrous ethanol and deionized water in sequence for 10-30 minutes each time, and then vacuum dried at 50-70°C to constant weight. The activator in step 1) is selected from any one or more of bromoisobutyryl bromide, acryloyl chloride, methacryloyl chloride, and benzoyl peroxide; the mass fraction of the activator in the solution containing the activator is 0.5% to 5%, and the surface hydroxyl activation treatment temperature is 0 to 25°C, and the time is 2 to 12 hours.
[0014] Furthermore, in step 2), the components in the aqueous reaction system are as follows by mass percentage: 2%~15% carboxyl monomer, 5%~25% polyether macromonomer, 0.05%~2% water-soluble initiator, and the balance is deionized water; wherein, the molar ratio of carboxyl monomer to polyether macromonomer is (1~6):1.
[0015] Further, in step 2), the mass ratio of the fiber to the total monomers in the aqueous reaction system is 1:(5~50); the water-soluble initiator is any one or more combinations of ammonium persulfate, potassium persulfate, azobisisobutyramazoline hydrochloride, hydrogen peroxide, and ascorbic acid; the temperature of the surface-initiated free radical copolymerization reaction is 50~85℃, the reaction time is 2~8 hours, and the pH value of the reaction system is 3~8; The carboxyl monomer is acrylic acid or methacrylic acid; the polyether macromonomer is any one or more of isopentenyl polyoxyethylene ether, allyl polyoxyethylene ether, and isobutylenyl polyoxyethylene ether.
[0016] Furthermore, in step 2), a chain transfer agent is added to the reaction system. The chain transfer agent is selected from any one or more of mercaptoacetic acid, mercaptopropionic acid, 3-mercaptopropionic acid, and 2-mercaptoethanol. The amount of chain transfer agent is 0.1% to 5% of the mass of the carboxyl monomer. In step 3), the washing process involves alternating between deionized water and anhydrous ethanol 3 to 6 times, and the drying temperature is 50 to 80°C for at least 6 hours.
[0017] In a second aspect, the present invention proposes a polyvinyl alcohol fiber prepared by the preparation method described in the first aspect, wherein the surface of the fiber is inherently anchored with a polycarboxylic acid-based water-reducing agent molecular brush structure by covalent bonds; the main chain of the molecular brush is a carboxyl polymer chain of polymethacrylic acid, and the side chains are polyoxyethylene segments; the grafting density of the polycarboxylic acid-based water-reducing agent on the fiber surface is 0.5~8 μmol / g fiber, and the grafting layer thickness is 5~200 nm.
[0018] Furthermore, the weight-average molecular weight (Mw) of the polycarboxylate superplasticizer grafted onto the fiber surface is 5000~80000; and the degree of polymerization of the polyoxyethylene side chain is 20~100.
[0019] In a third aspect, the present invention proposes an ultra-high performance concrete composition comprising cementitious materials, fine aggregates, quartz sand, steel fibers, polyvinyl alcohol fibers of the surface-in-situ synthesized polycarboxylate superplasticizer described in the second aspect, and freely added polycarboxylate superplasticizer; wherein the volume content of the polyvinyl alcohol fibers of the surface-in-situ synthesized polycarboxylate superplasticizer in the concrete is 0.3% to 2.0%.
[0020] Furthermore, the cementitious material includes any one or more of silicate cement, silica fume, fly ash microspheres, and slag powder, and the water-cement ratio of the concrete is not greater than 0.20.
[0021] In a fourth aspect, the present invention also proposes the application of polyvinyl alcohol fibers synthesized in situ from the surface of the polycarboxylate superplasticizer described in the second aspect in improving the workability and mechanical properties of ultra-high performance concrete, characterized in that the application includes at least one of the following: (a) Improve the uniformity of fiber dispersion in ultra-high performance concrete matrix; (b) Enhance the interfacial bond strength between the fiber and the cement matrix; (c) Microstructure of the dense interface transition zone; (d) Reduce the amount of admixture required for ultra-high performance concrete mixtures to achieve the target scalability.
[0022] Compared with the prior art, the present invention has the following advantages: 1. This invention, by in-situ grafting PCE molecular brushes onto the fiber surface, utilizes the steric hindrance effect of PEO side chains to establish a "soft barrier" between fibers, effectively blocking the hydrogen bond bridging channels between hydroxyl groups on the fiber surface, thus eliminating the root cause of agglomeration at the molecular level. The dispersion coefficient (FDC) of functionalized PVA fibers prepared using this method in a UHPC matrix is increased by 9.6% to 17.9% compared to unmodified fibers, and fiber agglomeration is significantly reduced.
[0023] 2. The functionalized fiber surface PCE molecular brush of the present invention simultaneously plays two interfacial enhancement roles: on the one hand, the carboxyl-COO groups on the PCE main chain... - It can react with the Ca released during cement hydration. 2+Ions coordinate and complex, promoting the directional growth of CSH gel on the fiber surface and densifying the ITZ microstructure. On the other hand, the covalently grafted PCE brush acts as a "molecular bridge" between the fiber and the matrix, improving the stress transmission path. In UHPC samples using the fibers of this invention, the fiber failure mode changes from pull-out dominant to fracture dominant, resulting in a substantial improvement in interfacial bonding strength.
[0024] 3. Because the fiber surface already carries PCE water-reducing function, it will gradually release local plasticizing effect during UHPC mixing. This means that the system's dependence on externally added free water-reducing agents is reduced. When UHPC using the fibers of this invention reaches the same spread (e.g., 200±5 mm), the free PCE content is significantly reduced by 12.5%~31.5% compared to the benchmark group (ordinary PVA fibers). This reduction effect not only has economic value, but more importantly, it optimizes the overall chemical balance of UHPC and avoids the retarding side effect caused by excessive free water-reducing agents.
[0025] 4. Benefiting from the synergistic effect of improved dispersibility and enhanced interface, the UHPC formulated with the fibers of this invention exhibits superior performance compared to the benchmark group in multiple mechanical properties: 28-day compressive strength increased by 5.3%~13.7%, 28-day flexural strength increased by 6.8%~14.8%, and 28-day energy absorption increased by 15.2%~26.4%. It is particularly noteworthy that these gains were achieved with a reduced dosage of the free water-reducing agent, demonstrating a true "efficiency enhancement and burden reduction" comprehensive benefit.
[0026] 5. The entire preparation process of this invention is based on an aqueous system, requiring no organic solvents. Only the activation step requires a small amount of organic medium. Subsequent polymerization and washing are carried out in an aqueous phase. The reaction conditions are mild, and the equipment requirements are basically the same as those of a conventional PCE production line. Both the fiber activation and grafting steps can be achieved using a continuous impregnation-reaction-washing production line, demonstrating good prospects for industrialization. Attached Figure Description
[0027] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0028] Figure 1 The infrared spectrum of the functionalized PVA fiber prepared in Example 1; Figure 2 The infrared spectrum of the functionalized PVA fiber prepared in Example 2; Figure 3The infrared spectrum of the functionalized PVA fiber prepared in Example 3; Figure 4 The infrared spectrum of the functionalized PVA fiber prepared in Comparative Example 2 is shown. Detailed Implementation To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] This invention provides a method for preparing polyvinyl alcohol fibers using polycarboxylate-based water-reducing agents synthesized in situ on the surface, comprising the following three core steps: Step S1: Activation of hydroxyl groups on the fiber surface and introduction of initiation sites. Commercially available PVA short-cut fibers are selected as raw materials. After ultrasonic cleaning with ethanol and water to remove surface impurities and thorough drying, they are immersed in an organic solution containing an activator for chemical modification of the surface hydroxyl groups. Preferably, 2-bromoisobutyryl bromide (BIBB) is used as the activator. The acyl bromide group in the BIBB molecule undergoes an esterification reaction with the hydroxyl groups on the PVA fiber surface, introducing α-hydroxyl groups onto the fiber surface. Bromoester groups are typical initiation sites for atom transfer radical polymerization (ATRP). By controlling the BIBB concentration, reaction temperature, and time, the density of initiation sites on the fiber surface can be precisely controlled, thereby pre-setting the growth density of the grafted polymer. In addition to BIBB, acyl halide compounds with polymerizable double bonds, such as acyl chloride and methacryloyl chloride, can also be used as activators, or peroxide initiators such as benzoyl peroxide (BPO) can be directly adsorbed and fixed on the fiber surface as a free radical source.
[0030] Step S2: Surface-initiated free radical copolymerization for in-situ synthesis of PCE molecular brushes. The functionalized fibers treated in Step S1 are transferred into an aqueous reaction system. This system contains two types of key monomers: one type is carboxyl monomers, such as AA acrylic acid or MAA methacrylic acid, used to construct the anionic backbone of PCE; the other type is polyether macromonomers, such as TPEG, APEG, and HPEG, which provide hydrophilic PEO side chains for a comb-like structure. A water-soluble free radical initiator, such as ammonium persulfate (APS), is added to the system, and the polymerization reaction is initiated at a controlled temperature. Since the fiber surface already has pre-placed initiation sites or is within the diffusion range of free radicals generated by the initiator decomposition, the polymerization reaction preferentially starts from the fiber surface. The carboxyl monomers and polyether macromonomers continuously add to and grow on the fiber surface, forming copolymer chains that extend outward from the fiber surface as the "root". This surface grafting method ensures that each polymer chain is connected to the fiber surface through covalent ester bonds or carbon-carbon bonds, resulting in a strong graft that is not easily desorbed.
[0031] Step S3: Post-processing purification. After the reaction is complete, the fiber is taken out and washed repeatedly with deionized water and anhydrous ethanol to remove unreacted monomers, homopolymers and residual initiators. Finally, it is dried to constant weight at a suitable temperature to obtain the functionalized PVA fiber product with PCE synthesized in situ on the surface.
[0032] The polyvinyl alcohol (PVA) fiber prepared by the above method using surface in-situ synthesis of polycarboxylate superplasticizers is characterized by a surface coating of a polycarboxylate superplasticizer molecular brush anchored by covalent bonds. The structure of this molecular brush is highly similar to that of conventional liquid PCE superplasticizers: the main chain is a carboxyl polymer chain of poly(meth)acrylic acid, and the side chains are polyoxyethylene (PEO) segments. Because the PCE molecular brush is directly "grown" on the fiber surface, the fiber acquires entirely new surface properties. The steric hindrance provided by the PEO side chains effectively shields the hydrogen bond interactions between residual hydroxyl groups on the fiber surface, fundamentally inhibiting fiber balling. Simultaneously, the carboxyl groups -COOH or -COO exposed on the outermost layer of the molecular brush... - It can exert the same electrostatic repulsion and steric hindrance dispersion effect as conventional PCE in the cement slurry pore liquid around the fiber, which is equivalent to each fiber having a local micro water reduction source.
[0033] This invention also provides an ultra-high performance concrete composition comprising the aforementioned functionalized fibers. In this UHPC composition, PVA fibers with in-situ synthesized PCE replace some or all of the conventional PVA fibers. Since the fibers themselves already possess water-reducing agent functionality, the amount of free PCE water-reducing agent that needs to be added to the system can be significantly reduced, by 10% to 35%, while maintaining the same spread. This "water-reducing agent reduction" effect not only saves on admixture costs but also avoids the excessive delaying effect of excessive free PCE on early hydration, contributing to better early strength development in UHPC.
[0034] The applications of the aforementioned functionalized fibers in UHPC include, but are not limited to: (a) improving the uniformity of fiber dispersion in the UHPC matrix; (b) enhancing the chemical bonding and stress transfer efficiency of the fiber-matrix interface; (c) densifying the ITZ microstructure and reducing interfacial porosity; and (d) reducing the amount of added water-reducing agent while maintaining the target workability.
[0035] Example 1: Preparation and UHPC Performance of Low Graft Density Functionalized PVA Fibers (1) Fiber surface activation: Weigh 50.0g of PVA fiber and ultrasonically clean it for 20 minutes each in anhydrous ethanol and deionized water (power 200W, frequency 40kHz). After cleaning, dry it in a vacuum drying oven at 60℃ to constant weight for about 8 hours, and record the weight as m0 = 49.82g. Immerse the dried fiber in 300mL of anhydrous THF and add 1.5mL of triethylamine as an acid-binding agent. Slowly add 2.0mL of bromoisobutyryl bromide under stirring in an ice bath at 0~5℃. After the addition is complete, continue the reaction at 0~5℃ for 3 hours, and then raise the temperature to room temperature (20~25℃) and continue the reaction for 3 hours. After the reaction is complete, wash it three times each with THF, anhydrous ethanol, and deionized water, and dry it in a vacuum oven at 60℃ to constant weight to obtain BIBB activated fiber with a mass of 51.06g.
[0036] (2) Surface-initiated copolymerization of PCE: Prepare an aqueous reaction system: 450g deionized water, 18.0g AA acrylic acid, 72.0g TPEG, and 1.35g ammonium persulfate (APS). Adjust the pH of the system to 5.5. Immerse all the above-mentioned BIBB activated fibers into the reaction system, heat to 65°C under nitrogen protection, and stir at a constant temperature for 4 hours. During the reaction, the viscosity of the system gradually increased, and the appearance of the fibers gradually changed from white to translucent.
[0037] (3) Post-treatment: After the reaction was completed, the fiber was removed and washed 5 times alternately with deionized water and anhydrous ethanol, with each washing liquid volume being about 500 mL. The fiber was then vacuum dried at 65 °C until constant weight was achieved. The final PVA fiber product with PCE grafted on the surface was obtained, with a mass of m1 = 54.27 g.
[0038] (4) Characterization results: Grafting rate G=[(54.27 [49.82) / 49.82] × 100% = 8.93%. (See attached diagram) Figure 1 As shown, the FTIR spectrum is displayed at 1724 cm⁻¹. -1 A distinct ester carbonyl stretching vibration peak was observed, attributed to BIBB esterification and PCE backbone carboxyl / ester groups, at 1112 cm⁻¹. -1 A strong COC ether bond stretching vibration peak appeared at the point, which belongs to the PEO segment of the TPEG side chain, proving that PCE was successfully grafted onto the fiber surface.
[0039] (5) UHPC Formulation and Performance Testing: The following UHPC baseline formulation was used, by mass: 1000 parts P·II 52.5 cement, 180 parts silica fume, 720 parts coarse silica sand, 480 parts fine silica sand; water-reducing agent, the amount was adjusted to achieve the target spread; 174 parts water, at a water-cement ratio of 0.15; steel fiber, 0.2 mm in diameter, 13 mm in length, 2.0 vol.%; PVA fiber, the product of this embodiment, 0.5 vol.% in amount, 12 mm in length. After trial mixing and adjustment, the amount of free PCE water-reducing agent required to achieve a spread of 200 mm was 1.75%, accounting for 1% of the mass of the adhesive. Compared with the baseline group, using the same amount of unmodified PVA fiber, the required amount of water-reducing agent was 2.00%, that is, this embodiment achieved a 12.5% reduction in water-reducing agent.
[0040] The UHPC performance comparison between Example 1 and the benchmark group is shown in Table 1 below.
[0041] Table 1. Comparison of UHPC performance between Example 1 and the benchmark group
[0042] As can be seen from Table 1, compared with the benchmark group, the UHPC prepared using PVA fiber in this embodiment has better 7d compressive strength, 28d compressive strength, 28d flexural strength and 28d energy absorption than the benchmark group.
[0043] Example 2: Preparation and UHPC Performance of Medium Graft Density Functionalized PVA Fibers (1) Fiber surface activation. The same cleaning and drying steps as in Example 1 were followed. 50.00 g of dried PVA fiber (m0) was immersed in 300 mL THF + 2.0 mL TEA, and 3.5 mL BIBB was added dropwise under ice bath conditions. The reaction was first carried out at 0-5 °C for 4 hours, and then at room temperature for 4 hours. After washing and drying, activated fiber with a mass of 52.01 g was obtained.
[0044] (2) Surface-initiated copolymerization to form PCE. Aqueous reaction system: 450g deionized water, 27.0g AA, 90.0g TPEG, 1.80g APS, 0.81g mercaptopropionic acid as chain transfer agent, accounting for 3% of the mass of AA, pH adjusted to 5.0. The activated fibers were completely immersed in the solution, and the temperature was raised to 70℃ under nitrogen protection and reacted at a constant temperature for 5 hours.
[0045] (3) Post-processing. Same as in Example 1, wash 6 times, and dry at 70°C to constant weight. Final product weight m1 = 59.84g.
[0046] (4) Characterization results. Grafting rate G=[(59.84 [50.00) / 50.00] × 100% = 19.68%. (Refer to the attached document.) Figure 2 As shown in the FTIR spectrum, compared to the original PVA fiber, the grafted fiber exhibits a higher density at 1724 cm⁻¹. -1 A new peak appeared, at 1724cm. -1 ester carbonyl peak and 1112 cm -1 The intensity of the ether bond peak was significantly increased compared to Example 1. This demonstrates the successful preparation of grafted density functionalized PVA fibers.
[0047] (5) UHPC formulation and performance testing. The same baseline formulation system as in Example 1 was used, with the PVA fiber content remaining at 0.5 vol.%. After trial mixing, the amount of free PCE water-reducing agent required to achieve the target spread of 200 mm was 1.53%, which represents a 23.5% reduction compared to the baseline group's 2.00%.
[0048] The UHPC performance comparison between Example 2 and the benchmark group is shown in Table 2 below.
[0049] Table 2 Comparison of UHPC performance between Example 2 and the benchmark group
[0050] The performance indicators of Example 2 are superior to those of Example 1 in all aspects, indicating that appropriately increasing the grafting density can achieve better overall results. In particular, the 28-day compressive strength exceeds 160 MPa and the flexural strength exceeds 26 MPa, reaching the upper limit of the high-performance range of UHPC.
[0051] Example 3: Preparation and UHPC Performance of High Graft Density Functionalized PVA Fibers (1) Fiber surface activation. The cleaning and drying steps are the same as in Example 1 above. Take 50.00g of dried PVA fiber (m0), immerse it in 300mL THF + 2.5mL TEA, and add 5.0mL BIBB dropwise under ice bath. React at 0~5℃ for 5 hours, then at room temperature for 5 hours. After washing and drying, activated fiber with a mass of 53.12g is obtained.
[0052] (2) Surface-initiated copolymerization to form PCE. Aqueous reaction system: 450g deionized water, 36.0g AA, 108.0g TPEG, 2.25g APS, 1.44g mercaptoacetic acid (4% of AA mass), pH adjusted to 4.5. The activated fibers were completely immersed in the solution, and the temperature was raised to 78℃ under nitrogen protection and reacted at a constant temperature for 6 hours.
[0053] (3) Post-processing. Same process as above, wash 6 times, and dry at 70℃ to constant weight. Final product weight m1 = 66.93g.
[0054] (4) Characterization results. Grafting rate G=[(66.93 [50.00) / 50.00] × 100% = 33.86%. (Refer to the attached document.) Figure 3 As shown, the peak intensities of the ester carbonyl group and ether bond in the FTIR spectrum are further enhanced.
[0055] (5) UHPC formulation and performance testing. The same baseline formulation system as in Example 1 was used, with a PVA fiber content of 0.5 vol.%. The free PCE content required to achieve the target spread of 200 mm was 1.37%, which is 31.5% lower than the baseline group's 2.00%.
[0056] The UHPC performance comparison between Example 3 and the benchmark group is shown in Table 3 below.
[0057] Table 3. Comparison of UHPC performance between Example 3 and the benchmark group
[0058] It is worth noting that the 7-day compressive strength increase of +8.3% in Example 3 is slightly lower than the +9.4% increase in Example 2. This indicates that excessively high grafting density may have a certain degree of delaying effect on early hydration, and an excessively thick PCE molecular brush layer will chelate too much Ca in the early stages. 2+ The ions locally slowed down the hydration rate of C3S. However, the indicators at 28 days were still the best among the three, indicating that the advantages of interface densification and dispersion improvement brought about by high grafting density are dominant in the long run.
[0059] Comparative Example 1: Unmodified PVA fibers, i.e., the baseline control group Commercially available PVA fibers (12 mm in length, 39 μm in diameter) were used directly in the UHPC formulation without any surface treatment. The UHPC formulation used the same baseline formulation system as in Example 1, with PVA fiber content of 0.5 vol.% and steel fiber content of 2.0 vol.%. The required free PCE water-reducing agent content to achieve an extension of 200 mm was 2.00%. Performance data are shown in the baseline group in Tables 1-3.
[0060] Comparative Example 2: Physical Adsorption PCE Coating of PVA Fibers Preparation method: Take 50.00g of unmodified PVA fiber and immerse it in 500mL of a 5wt.% aqueous solution of conventional PCE water-reducing agent (i.e., dilute the solid content to 5% for impregnation). Stir magnetically at room temperature for 24 hours. After removal, vacuum dry at 65℃ to constant weight. This method does not involve any chemical activation or covalent grafting steps; PCE adheres to the fiber surface solely through physical adsorption, electrostatic attraction, and hydrogen bonding.
[0061] Characterization: The adsorption weight gain rate measured by gravimetric method was 4.62%, far lower than the covalent grafting rate of the example. After soaking and washing in deionized water for 2 hours and then weighing again, the weight gain rate decreased to 0.87%, indicating that most of the adsorbed PCE can be desorbed and removed in water. (Refer to Appendix) Figure 4 As shown, no new characteristic peaks were observed in the FTIR spectrum; only the existing PVA and trace PCE signals were superimposed.
[0062] UHPC Performance: The UHPC formulation uses the same baseline formulation system as Comparative Example 1. The required free PCE water-reducing agent dosage to achieve the target spread of 200mm is 1.91%, a 4.5% reduction compared to the baseline group, significantly less than the 12.5%~31.5% reduction range of Examples 1-3. 28-day compressive strength is 149.7 MPa; 28-day flexural strength is 24.13 MPa; fiber dispersion factor (FDC) is 0.312. All gains are significantly lower than in Examples 1-3.
[0063] A comparison of the UHPC performance obtained in Comparative Example 2 with that in Examples 1-3 shows that simple physical adsorption cannot achieve a stable integrated water-reducing agent-fiber function. PCE rapidly desorbs into free water during mixing, losing its specific dispersion effect on the fiber. This demonstrates the necessity and irreplaceability of the covalent grafting strategy employed in this invention.
[0064] Comparative Example 3: KH560 silane treatment of PVA fibers Preparation method: PVA fibers are immersed in a 95% ethanol aqueous solution of 3 wt.% KH560 silane coupling agent, the pH is adjusted to 4.5~5.5, and soaked at room temperature for 2 hours. After being taken out, they are cured in an oven at 105℃ for 1 hour.
[0065] UHPC Performance: The UHPC formulation uses the same baseline formulation system as Comparative Example 1. The required free PCE content to achieve the target spread of 200 mm is 1.96%, only 2.0% lower than the baseline group, with almost no water-reducing agent reduction effect, because KH560 itself does not have water-reducing function. The 28-day flexural strength is 27.17 MPa, which is higher than the flexural strength increase in Examples 1-3, confirming the effective strengthening effect of KH560 on interfacial adhesion. However, the 28-day compressive strength is 151.2 MPa; the energy absorption is 7430 J, both lower than the levels in Examples 2 and 3.
[0066] This demonstrates that KH560 silane treatment effectively enhances the fiber-matrix interface, particularly flexural strength. However, due to its lack of fiber dispersion and water-reducing properties, its improvement on the workability and overall mechanical properties of UHPC is limited. The PCE grafted fiber of this invention, on the other hand, possesses the triple benefits of "fiber dispersion + interface strengthening + localized water reduction," representing a more comprehensive solution.
[0067] Comparative Example 4: Functionalized PVA Fibers with Excessively High Grafting Density Preparation method: The process route of Example 3 was followed, but the amount of BIBB was increased to 8.0 mL, which is 1.6 times that of Example 3; AA was increased to 48.0 g; TPEG was increased to 144.0 g; the reaction temperature was increased to 85°C; and the reaction time was extended to 8 hours. All other parameters remained unchanged. The resulting PVA fibers had a grafting rate as high as 47.3%, and the fibers had a semi-transparent gel-like appearance and a sticky feel.
[0068] Although the dosage of free PCE water-reducing agent was further reduced to 1.18%, a 41% reduction compared to the baseline group, the mechanical properties of UHPC actually declined across the board: the 7-day compressive strength was 108.6 MPa, lower than the baseline group's 118.3 MPa; the 28-day compressive strength was 158.3 MPa; the 28-day flexural strength was 25.01 MPa; and the energy absorption was 7621 J. All data were lower than the optimal examples 2 and 3.
[0069] This shows that excessively high grafting density may lead to the following negative effects: (a) an excessively thick PCE molecular brush layer severely hinders the penetration and chemical bonding of cement hydration products to the fiber surface, thus isolating the interface; (b) a large number of carboxyl groups excessively chelate Ca in the local fiber area. 2+ (c) The excessively thick polymer layer reduced the stiffness contribution and frictional bonding component of the fiber itself.
[0070] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing polyvinyl alcohol fibers using a surface-in-situ synthesis of a polycarboxylate-based water-reducing agent, characterized in that, Includes the following steps: 1) Polyvinyl alcohol fibers are immersed in a solution containing an activator to perform surface hydroxyl activation treatment, thereby introducing free radical polymerization initiation sites on the fiber surface to obtain fibers with initiation sites functionalized. 2) The fiber obtained in step 1) is placed in an aqueous reaction system containing carboxyl monomers and polyether macromonomers. Under the action of a water-soluble initiator, a surface-initiated free radical copolymerization reaction is carried out, so that the polycarboxylate superplasticizer is grafted and grown in situ from the fiber surface in the form of covalent bonds, forming a functionalized fiber with a polycarboxylate superplasticizer molecular brush on the surface. 3) The fibers obtained in step 2) are washed and dried to obtain polyvinyl alcohol fibers with polycarboxylic acid water-reducing agents synthesized in situ on the surface.
2. The method for preparing polyvinyl alcohol fibers using surface in-situ synthesis of polycarboxylate superplasticizers according to claim 1, characterized in that, In step 1), the polyvinyl alcohol fibers are pre-cleaned and solvent-replaced before the surface hydroxyl activation treatment; the specific steps are as follows: The fibers were ultrasonically cleaned with anhydrous ethanol and deionized water in sequence for 10 to 30 minutes each time, and then vacuum dried at 50 to 70°C until constant weight. The activator in step 1) is selected from any one or more of bromoisobutyryl bromide, acryloyl chloride, methacryloyl chloride, and benzoyl peroxide; the mass fraction of the activator in the solution containing the activator is 0.5% to 5%, and the surface hydroxyl activation treatment temperature is 0 to 25°C, and the time is 2 to 12 hours.
3. The method for preparing polyvinyl alcohol fibers using surface in-situ synthesis of polycarboxylate superplasticizers according to claim 1, characterized in that, In step 2), the components in the aqueous reaction system are as follows by mass percentage: 2%~15% carboxyl monomer, 5%~25% polyether macromonomer, 0.05%~2% water-soluble initiator, and the balance is deionized water; wherein, the molar ratio of carboxyl monomer to polyether macromonomer is (1~6):
1.
4. The method for preparing polyvinyl alcohol fibers using surface in-situ synthesis of polycarboxylate superplasticizers according to claim 1, characterized in that, In step 2), the mass ratio of the fiber to the total monomers in the aqueous reaction system is 1:(5~50); the water-soluble initiator is any one or more combinations of ammonium persulfate, potassium persulfate, azobisisobutyramazoline hydrochloride, hydrogen peroxide, and ascorbic acid; the temperature of the surface-initiated free radical copolymerization reaction is 50~85℃, the reaction time is 2~8 hours, and the pH value of the reaction system is 3~8; The carboxyl monomer is acrylic acid or methacrylic acid; the polyether macromonomer is any one or more of isopentenyl polyoxyethylene ether, allyl polyoxyethylene ether, and isobutylenyl polyoxyethylene ether.
5. The method for preparing polyvinyl alcohol fibers using surface in-situ synthesis of polycarboxylate superplasticizers according to claim 1, characterized in that, Step 2) A chain transfer agent is also added to the reaction system. The chain transfer agent is selected from any one or more of mercaptoacetic acid, mercaptopropionic acid, 3-mercaptopropionic acid, and 2-mercaptoethanol. The amount of chain transfer agent is 0.1% to 5% of the mass of the carboxyl monomer. In step 3), the washing process involves alternating between deionized water and anhydrous ethanol 3 to 6 times, and the drying temperature is 50 to 80°C for at least 6 hours.
6. A polyvinyl alcohol fiber prepared by the preparation method according to any one of claims 1 to 5, characterized in that, The fiber surface is anchored by covalent bonds to the molecular brush structure of the polycarboxylate superplasticizer; the main chain of the molecular brush is a carboxyl polymer chain of polymethacrylic acid, and the side chain is a polyoxyethylene segment; the grafting density of the polycarboxylate superplasticizer on the fiber surface is 0.5~8 μmol / g fiber, and the grafting layer thickness is 5~200 nm.
7. Polyvinyl alcohol fiber with polycarboxylate superplasticizer synthesized in situ according to claim 6, characterized in that, The weight-average molecular weight (Mw) of the polycarboxylate superplasticizer grafted onto the fiber surface is 5000~80000; the degree of polymerization of the polyoxyethylene side chain is 20~100.
8. A high-performance concrete composition, characterized in that, The concrete comprises cementitious materials, fine aggregates, quartz sand, steel fibers, polyvinyl alcohol fibers of the surface-in-situ synthesized polycarboxylate superplasticizer as described in claim 6 or 7, and freely added polycarboxylate superplasticizer; wherein the volume content of the polyvinyl alcohol fibers of the surface-in-situ synthesized polycarboxylate superplasticizer in the concrete is 0.3% to 2.0%.
9. The ultra-high performance concrete composition according to claim 8, characterized in that, The cementitious material includes any one or more of silicate cement, silica fume, fly ash microspheres, and slag powder, and the water-cement ratio of the concrete is not greater than 0.
20.
10. The application of polyvinyl alcohol fibers synthesized in situ from surface-based polycarboxylate superplasticizers as described in claim 6 or 7 in improving the workability and mechanical properties of ultra-high performance concrete, characterized in that... The application includes at least one of the following: (a) Improve the uniformity of fiber dispersion in ultra-high performance concrete matrix; (b) Enhance the interfacial bond strength between the fiber and the cement matrix; (c) Microstructure of the dense interface transition region; (d) Reduce the amount of admixture required for ultra-high performance concrete mixtures to achieve the target scalability.